1994
DOI: 10.1121/1.410558
|View full text |Cite
|
Sign up to set email alerts
|

Resonances of deformed gas bubbles in liquids

Abstract: A T-matrix expansion technique has been used to investigate the monopole acoustical resonances of bubbles deformed into elongated axisymmetric objects (specifically: prolate spheroids and cylinders with hemispherical endcaps). The bubbles are modeled as air-filled inclusions in water. Scattering occurs because of the change of acoustical impedance at the interface between the two media. The results confirm that the resonance frequency of a bubble increases when it is deformed from a spherical shape. It increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…However, near resonance, it has been shown that the acoustic response, whether assuming a spherical, spheroidal, or cylindrical air-bubble model, generally varies by at most 30% [47][48]. Accordingly, as a first approximation we consider a spherical swimbladder, and then introduce corrections to account for real fish.…”
Section: Swimbladder Propertiesmentioning
confidence: 99%
“…However, near resonance, it has been shown that the acoustic response, whether assuming a spherical, spheroidal, or cylindrical air-bubble model, generally varies by at most 30% [47][48]. Accordingly, as a first approximation we consider a spherical swimbladder, and then introduce corrections to account for real fish.…”
Section: Swimbladder Propertiesmentioning
confidence: 99%
“…In addition, low ka resonance scattering by gaseous bodies of higher aspect ratio (up to 100:1) was calculated with no difficulties relative to the numerical issues cited earlier. These ratios are much higher than what 39 has previously appeared in the literature (Strasberg, 1953;Weston, 1967;Feuillade and Werby, 1994;Ye and Hoskinson, 1998) There is great potential for further development of this model, including application to acous-tic scattering by elastic solids and shells. The implementation of better numerical integration techniques, the use of extended precision format of floating point arithmetic or various smoothing techniques (Yamashita, 1990) could delay the onset of ill-conditioned matrices, accelerating convergence.…”
Section: Irregular Bodies: Comparison With Kirchhoff Approximationmentioning
confidence: 71%
“…Predictions from the T-matrix method and FMM are compared in Fig. 13 for aspect ratios up to 16:1; however, results for aspect ratios up to 20:1 were presented by Feuillade and Werby (1994) using the T-matrix method, as well as Ye and Hoskinson (1998) using the exact prolate spheroidal solution. In addition, low ka resonance scattering by gaseous bodies of higher aspect ratio (up to 100:1) was calculated with no difficulties relative to the numerical issues cited earlier.…”
Section: Irregular Bodies: Comparison With Kirchhoff Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…Small variations from spherical conditions are not believed to significantly affect the bubble res-onance 18 since a prolate spheroid of aspect ratio of 1.414 only varies in resonance frequency and damping from a spherical bubble by less that 1%. 19 The volume of each balloon was measured through the water it displaced when submerged, then the equivalent spherical radius was determined as the radius that would displace the same volume of water. Six balloons with equivalent spherical radii of 2 cm were attached to a monofilament nylon line so that there was an L/6 distance between each balloon and an L/12 distance between each end balloon and a termination, where L is the length of the water column in the pipe.…”
Section: Introductionmentioning
confidence: 99%